Differential expression of CD49a and CD49b determines localization and function of tumor-infiltrating CD8(+) T cells - Melssen, Marit M. (Cancer Immunol Res, 2021)
CD8(+) T-cell infiltration and effector activity in tumors are correlated with better overall survival of patients, suggesting that the ability of T cells to enter and remain in contact with tumor cells supports tumor control. CD8(+) T cells express the collagen-binding integrins CD49a and CD49b, but little is known about their function or how their expression is regulated in the tumor microenvironment (TME). Here, we found that tumor-infiltrating CD8(+) T cells initially expressed CD49b, gained CD49a, and then lost CD49b over the course of tumor outgrowth. This differentiation sequence was driven by antigen-independent elements in the TME, although T-cell receptor (TCR) stimulation further increased CD49a expression. Expression of exhaustion markers and CD49a associated temporally, but not mechanistically. Intratumoral CD49a-expressing CD8(+) T cells failed to upregulate TCR-dependent Nur77 expression, while CD69 was constitutively expressed, consistent with both a lack of productive antigen engagement and a tissue-resident memory-like phenotype. Imaging T cells in live tumor slices revealed that CD49a increased their motility, especially of those in close proximity to tumor cells, suggesting that it may interfere with T-cell recognition of tumor cells by distracting them from productive engagement, although we were not able to augment productive engagement by short-term CD49a blockade. CD49b also promoted relocalization of T cells at a greater distance from tumor cells. Thus, our results demonstrate that expression of these integrins impacts T-cell trafficking and localization in tumors via distinct mechanisms, and suggests a new way in which the TME, and likely collagen, could promote tumor-infiltrating CD8(+) T-cell dysfunction.